Pengaruh Media Audio Visual Terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika Kelas V di SDN Cipari - Nurfadilah, Yusril; Loustiawaty, Lousy (Indo-MathEdu Intellectuals Journal, 2025)
The background of this study is the low interest and learning outcomes of students in understanding abstract Mathematics concepts. This study aims to determine the effect of using audiovisual media on student learning outcomes in Mathematics. The research method used was a quantitative method with a quasi-experimental design. The population in this study were fifth-grade students at Cipari Public Elementary School, with a purposively selected sample. The data collection instrument was a learning achievement test administered before (pre-test) and after (post-test) the treatment. The results of the data analysis showed a significant improvement in the learning outcomes of students who used audiovisual media compared to students who studied without such media. Audiovisual media has been shown to help students better understand the material through the presentation of interesting and interactive information. Thus, it can be concluded that the use of audiovisual media has a positive effect on improving students' Mathematics learning outcomes.